Sustainable Solutions in the Hospitality Industry and Competitiveness Context of “Green Hotels” - Tamara Floričić (Civil Engineering Journal, 2020)
This interdisciplinary paper researches the importance of sustainable hotel engineering and organisation of facilities for the purposes of realisation of a sustainable and responsible hospitality facility business. Considered through the interdisciplinary aspect, at the same time, it represents a research goal with the focus on the segment of youth tourists, who, as existing consumers of low-budget expenditure, are turning into DINKY, as well as the segment of conscious adult consumers in the future. The paper, through a questionnaire, researches the perception of the importance of resource management, with the implementation of innovative technologies by youth tourists’ related attitudes and experiences. The methodology is based predominantly on qualitative research methods and includes analysis and conceptual methodology and survey research methods of youth tourists’ attitudes. The quantitative research was processed by using the statistical methodology combined with techniques of creative thinking formation. The results point to the predominance of importance in which over 90% of respondents confirm the importance of sustainable initiatives and resource management with the following rank: food, water, energy, and waste management. Further analysis implies an opposite attitude where only 52.9% of participants would be willing to pay higher prices for sustainable solutions in hotels. The results and recommendations contribute to knowledge and ideas by recognizing competitiveness of hotels, which design and engineer the business system and operations with support of sustainable technologies in an interdisciplinary way. The paper also contributes to the comprehension of combined and successfully communicated economic and marketing values of sustainable innovations supported by digital technologies.